Pengaruh Rasio Keuangan terhadap Harga Saham: Studi pada Perusahaan Properti dalam Indeks Kompas100 - Fadawkas, Reza Risyad; Nursanta, Edy; Widiyarsih, Widiyarsih; Masitoh, Siti (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return on Equity (ROE), and Price to Book Value (PBV) on the stock price of property sub-sector companies in the Kompas100 Index for the 2019-2023 period. The type of data used is secondary data, with purposive sampling. The analysis uses the classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. Based on the discussion that has been carried out on the effect of Debt to Equity Ratio (DER), Return on Equity (ROE), and Price to Book Value (PBV) on the Stock Price of property sub-sector companies listed in the Kompas100 Index for the 2019-2023 period, it can be concluded that the Debt to Equity Ratio (DER) variable has a significant negative effect on the Stock Price of property sub-sector companies listed in the Kompas100 Index for the 2019-2023 period. The Return on Equity (ROE) variable has a significant negative effect on the Stock Price of property sub-sector companies listed on the Kompas100 Index for the 2019-2023 Period. The Price to Book Value (PBV) variable has a significant positive effect on the Stock Price of property sub-sector companies listed on the Kompas100 Index for the 2019-2023 Period. Debt to Equity Ratio (DER), Return on Equity (ROE), and Price to Book Value (PBV) have a significant effect on the Stock Price of property sub-sector companies listed on the Kompas100 Index for the 2019-2023 Period. The Price to Book Value (PBV) variable has the most dominant effect on the Stock Price of property sub-sector companies listed on the Kompas100 Index for the 2019-2023 Period.